Multiple Bladder Diverticula Presenting in an 82-Year-Old Congolese Male - Jean de Dieu Tumusifu Manegabe; Daniel Safari Nteranya; Ghislain Maheshe Balemba; Fabrice Cikomola Gulimwentuga; Paul Budema Munguakonkwa; Paterne Safari Mudekereza; Bijou Safi Matabaro; Alliance Wani Bisimwa; Franck Masumbuko Mukamba; Georges Kuyigwa Toha; Kizito Mutuga Centwali; Costa Sudi Musilimu; et al. (Case Reports in Surgery)
Bladder diverticulum is a congenital malformation characterized by the outpouching of the bladder following an obstruction of urine flux. We present a case of 82-year-old Congolese male patient presented at our facility with a poor urinary stream and lower abdominal pain. A distended abdomen was found on physical examination while the external genitalia were normal. All blood laboratory values were found to be within normal ranges. The patient’s urine analysis revealed an uncountable number of white blood cells. Ultrasonography revealed multiple diverticula in the right posterolateral and posterior wall. An ultrasound of the abdomen revealed numerous bladder diverticula in the bladder’s left posterolateral and posterior aspects, mild right-sided hydronephrosis, and severe left hydronephrosis with a thinned-out cortex. Both ureters were normal. A computed tomographic (CT) scan of the abdomen confirmed the diagnosis. The patient underwent an open laparotomy which allowed complete ablation of the diverticula followed by bladder wall repair. A one-week course of antibiotics was prescribed, and the patient was discharged fully recovered with no immediate complications. Although bladder diverticula are a congenital malformation, the presence of multiple diverticula suggests that the condition is acquired. In elderly patients, open laparotomy combined with intravenous antibiotics yields positive results.